A ATUAÇÃO DO COORDENADOR PEDAGÓGICO JUNTO ÀS SALAS DE RECURSOS MULTIFUNCIONAIS - MACHADO, Suely Alves dos Santos (2022)
In this dissertation we present the results of the research about the performance of the pedagogical coordinator in the multifunctional rooms of schools in the State of Maranhão, located in pole IV of the capital São Luís. To do so, we start from a study on inclusive education in Brazil, in which we rescue special education, as well as the presentation of AEE as a support in the process of school inclusion. Inclusion is a topic of great relevance, which has aroused the interest of many scholars about the legal framework and pedagogical practices that contribute or hinder the progress of the process at school. Providing inclusion in the school space is welcoming, it is promoting accessibility, it is providing practices that result in the learning and socialization of all individuals. In view of this perspective, we aimed to analyze the pedagogical coordinator's practices implemented in state schools, especially their contributions to the effective learning of students with special needs in multifunctional resource rooms. In addition, we sought to verify if the multifunctional resource room offers conditions for the schooling of the target public student of special education; identify which activities are suggested by the pedagogical coordinator in relation to the pedagogical practices of the teachers of the multifunctional resource room and analyze the actions and practices implemented by the pedagogical coordinator aimed at the inclusion of special education students. The methodology it was based on the dialectical method, in which we simultaneously included field research and bibliographic research, thus covering the theory of approach (the method), the instruments for operationalization of knowledge (the techniques) and the researcher's creativity. The results found show that teachers and pedagogical coordinators, who work in the schools visited, are aware of the laws that guarantee adequate care for students with disabilities, they are aware of the relevance of the role of the pedagogical coordinator and of the multifunctional rooms for specialized educational service. However, these professionals consider that there are still obstacles in this service. The lack of training of teachers to work with special education is the main one, as well as the lack of physical structure and didactic material, which are part of the apparatus to develop qualitative work that complies with the legal proposals for the inclusion process. We also noticed the need for interaction between teachers from the resource room and regular education teachers. Finally, we found that the coordinator's performance needs to improve and that training is essential for the work to evolve.